Mapping the Research Landscape on Demographic Ageing and Economic Growth: A Bibliometric Analysis - LITRĂ Adriana Veronica (Economies, 2026)
Demographic ageing, a topic that is intensively addressed in the scientific literature, significantly influences the functioning of economic systems. Demographic ageing directly impacts the labour supply, productivity, savings, investments and the sustainability of public finances through pressure on pension and health systems. However, the efforts of ageing societies to transform and adapt to this demographic challenge through economic restructuring and innovation are recognized. Starting from the growing interest shown in the link between the demographic transformation of a society and the economic impact, the study carries out a bibliometric analysis on a dataset of 934 documents included in the OpenAlex platform, selected by filtering scientific publications according to a set of predefined criteria. The analysis of thematic clusters, co-authorship and bibliographic coupling reveals an increase in interdisciplinary research and a shift in emphasis from classical macroeconomic effects on the labour market and the financial system towards multidimensional transformations of the economic and social system, in which demographic transformation is no longer just a constraint but also a challenge towards progress through the integration of digitalization, automation and transition to AI-based economic systems to support economic development.
Keywords: demographic ageing; economic growth; bibliometric analysis; VOSviewer; OpenAlex